2022
DOI: 10.3390/ijms23116085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Linkers and Substitutions on Multitarget Directed Ligands for Alzheimer’s Diseases: Emerging Paradigms and Strategies

Abstract: Alzheimer’s disease (AD) is multifactorial, progressive and the most predominant cause of cognitive impairment and dementia worldwide. The current “one-drug, one-target” approach provides only symptomatic relief to the condition but is unable to cure the disease completely. The conventional single-target therapeutic approach might not always induce the desired effect due to the multifactorial nature of AD. Hence, multitarget strategies have been proposed to simultaneously knock out multiple targets involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Nonetheless, a multitude of compelling studies have reported that they can act only for limited periods and present a risk of harmful side effects. To overcome these drawbacks, researchers are eager to find and develop innovative candidates to combat this disorder. In this line, burgeoning evidence revealed that a wide range of selenocompounds has great effectiveness in AD. …”
Section: Selenized Small Molecule Drugsmentioning
confidence: 99%
“…Nonetheless, a multitude of compelling studies have reported that they can act only for limited periods and present a risk of harmful side effects. To overcome these drawbacks, researchers are eager to find and develop innovative candidates to combat this disorder. In this line, burgeoning evidence revealed that a wide range of selenocompounds has great effectiveness in AD. …”
Section: Selenized Small Molecule Drugsmentioning
confidence: 99%
“…Given the multifactorial nature of their pathogenicity, neurodegenerative diseases, such as Alzheimer's disease, appear to be able to respond positively to treatment with pleiotropic compounds, provided that they can be administered precociously through the early diagnostic stage which still needs to be improved. Some studies have recently focused on this approach [4][5][6]. Overall, the literature reports four types of pleiotropic agents designed for the potential management of Alzheimer's disease (Figure 2).…”
Section: The Application Of the Concept Of Pleiotropic Active Compoun...mentioning
confidence: 99%
“…Over the years, molecules containing both melatonin scaffold and a donepezil fragment have been demonstrated to possess strong inhibitory activity against acetylcholinesterase [ 19 , 20 , 21 , 22 ]. Melatonin holds promise as a potential therapeutic agent for developing new multitarget hybrids against neurodegeneration, including AD, because it can modulate the balance of Aβ production/clearance and mitigate Aβ neurotoxicity [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%